1988
DOI: 10.1021/bi00412a018
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of carbonic anhydrase-4-fluorobenzenesulfonamide complexes

Abstract: Binding of 4-fluorobenzenesulfonamide to human carbonic anhydrases I and II has been studied by proton, fluorine, and nitrogen-15 nuclear magnetic resonance spectroscopy. All three types of experiments provide evidence that the stoichiometry of the interaction of this inhibitor with both enzymes is 2 mol of inhibitor bound per mole of enzyme. Observations which suggest that the bound forms are involved in an exchange process that is rapid at room temperature but slower at 2 degrees C are described. Nitrogen-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…This observation is in contrast to the results reported by Gerig and co-workers. [19,20] On the basis of binding titrations followed by 19 F NMR spectroscopy, these investigators reported that 2-FBS, 3-FBS, and 4-FBS bound with ligand-to-protein stoichiometries of 2:1 in complexes with HCA I and II, and that the bound ligands were in fast exchange on the NMR timescale (and thus were likely to be in the active site). [19,20] These results are very surprising given the 1:1 stoichiometry that has been demonstrated for almost all other sulfonamide-wild-type CA complexes by a number of biophysical techniques.…”
Section: The Outlier: 4-fluorobenzenesulfonamidementioning
confidence: 99%
See 4 more Smart Citations
“…This observation is in contrast to the results reported by Gerig and co-workers. [19,20] On the basis of binding titrations followed by 19 F NMR spectroscopy, these investigators reported that 2-FBS, 3-FBS, and 4-FBS bound with ligand-to-protein stoichiometries of 2:1 in complexes with HCA I and II, and that the bound ligands were in fast exchange on the NMR timescale (and thus were likely to be in the active site). [19,20] These results are very surprising given the 1:1 stoichiometry that has been demonstrated for almost all other sulfonamide-wild-type CA complexes by a number of biophysical techniques.…”
Section: The Outlier: 4-fluorobenzenesulfonamidementioning
confidence: 99%
“…[19,20] On the basis of binding titrations followed by 19 F NMR spectroscopy, these investigators reported that 2-FBS, 3-FBS, and 4-FBS bound with ligand-to-protein stoichiometries of 2:1 in complexes with HCA I and II, and that the bound ligands were in fast exchange on the NMR timescale (and thus were likely to be in the active site). [19,20] These results are very surprising given the 1:1 stoichiometry that has been demonstrated for almost all other sulfonamide-wild-type CA complexes by a number of biophysical techniques. [1,45,46] In search of a reconciliation between these conclusions, we speculated that Gerig and co-workers might have been observing a second, weak binding site (K d obs % 5 mm) that we would not observe under the conditions we used for ITC, because of the greater (50-100-fold) concentration of CA used in NMR spectroscopy (0.5-1 mm) than in ITC (10 mm).…”
Section: The Outlier: 4-fluorobenzenesulfonamidementioning
confidence: 99%
See 3 more Smart Citations